Padrões de citação em comunicação: análise das dissertações apresentadas à ECO/UFRJ - Cavalcanti, Ilce Gonçalves Milet (1989)
This work analyses the studies produced at UFRJ/ECO in the area of Communication, with the intention of singling out the general behavior of researchrs, through its intellectual guide-lines. The research covers the M.A. dissertations produced as research tools, beint considered the patterns of quotation there used. So, it is possible to identify both the means of Communications used, as well as to establish the representative core of journals refered to, besides delimiting the half-life the journals, also checking the quantity of documental sources, so as to compare those patterns with the one prevailing at the area of Information Science at the same Institution. The most referred means of communication are the book (71,20%) and the journal (13,80%). The measured half-life of books is about 8 years and journals, 3 years. The most frequent language is Portuguese (71,35%) followed by French (15,42%). A Brazilian journal (1%) concentrates 12,3% of the whole quotations and 12,6% of the whole of quotations are dispersed throught 39 journals (37,1%). The national publication in journal form that gathers most frquent quotations is Veja, an informative publication. Two foreign journals (2,5,%) gather 23% of the whole quotations are dispersed throught 41 journals (51,2%). The most frequently quoted foreign journals are: Communications (Paris) and Ottagono (Milan). The present dissertation compares those results with similar variables in the area of Information Science and reaches the conclusion that theyare fields of Studies the very different characteristics.